Psychodynamic of Forest Conserving Behavior in Muria Forest Community - Widjanarko, Mochamad; Suryanto; Mashud, Mustain x (International Journal of Psychosocial Rehabilitation, 2020)
Muria Mountains that extends into Kudus, Jepara and Pati districts have a primary function as a buffer for plant and wildlife ecosystems. It also effects the Muria forest’s people living because it is the clean water supply for the surrounding area. This study aims to analyze and discover the psychodynamic of forest conserving behavior in Muria forest community. This research uses qualitative approach with grounded theory. There were seven informants involved in this study. The researcher uses in-depth interviews and observations in the process of extracting data and analyzing. The integrated ecological behavior model, that is based on the combination of Kurt Lewin field theory and Kaiser's ecological behavior, is a research finding which can examine the psychodynamic of forest conserving behavior in Muria forest community. It is based on the informants’ expectation in maintaining the Muria forest as a sense of responsibility for Muria's damage, so that it brings environmental values to maintain the Muria forest. Besides, there is an awareness on the need of water for farmer based on the knowledge of the informant in maintaining the Muria forest, the emergence of encouragement to maintain the Muria forest after the disaster and barrier in conserving the Muria forest. It is undeniable that there is an economic need that encourages informants in maintaining the Muria forest and conserving the Muria forest from others and related to the land ownership which is part of the responsibility of maintaining the Muria forest. At last, the emergence of caring for the Muria forest becomes an environmental value.